Street Level Bureaucracy Dalam Pelaksanaan Penanganan Stunting di Kabupaten Sidoarjo - Andrea Caesarinda Daffa Ardhana; Dida Rahmadanik; Adi Soesiantoro (Universitas 17 Agustus 1945 Semarang, 2025)
Street-level bureaucracy refers to the role of frontline bureaucrats who directly engage with the public in the implementation of public policies, including stunting management. In Sidoarjo Regency, stunting remains a critical public health issue with long-term implications for human capital development, despite the government’s continuous efforts to reduce its prevalence. Actors such as posyandu cadres, health center personnel, and officials from the District Health Office serve as the front line in detecting stunting cases, delivering nutritional counseling, monitoring child growth, and connecting communities with essential health services. However, the effectiveness of these roles is often constrained by limited resources, excessive workloads, lack of adequate training, and insufficient incentives that do not reflect the complexity of their responsibilities. Furthermore, policy implementation is frequently hindered by weak inter-sectoral coordination, low community engagement, and the gap between administrative guidelines and the realities faced in the field. The discretionary power held by these street-level bureaucrats becomes both a strength and a challenge—allowing for flexible adaptation to local needs while raising concerns about accountability and service consistency. Addressing stunting effectively at the local level requires strategic capacity-building for implementers through continuous training, fair compensation, and strengthened collaboration among governmental actors and other stakeholders. These efforts must be integrated, holistic, and sustainable in order to truly tackle the root causes of stunting and generate meaningful improvements in public health outcomes.